1985
DOI: 10.1037/0003-066x.40.11.1189
|View full text |Cite
|
Sign up to set email alerts
|

Response expectancy as a determinant of experience and behavior.

Abstract: Response expectancies, defined as expectancies of the occurrence of nonvolitional responses, have generally been ignored in theories of learning. Research on placebos, hypnosis, and fear reduction indicates that response expectancies generate corresponding subjective experiences. In many cases, the genuineness of these self-reported effects has been substantiated by corresponding changes in behavior and physiological function. The means by which response expectancies affect experience, physiology, and behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
728
3
13

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 899 publications
(782 citation statements)
references
References 126 publications
(171 reference statements)
38
728
3
13
Order By: Relevance
“…Expectation of placebo analgesia was not significantly correlated with placebo response (r Ā¼ 0.19, P Ā¼ 0.19), while the difference between subjectively assessed and initially expected efficacy, which represents a measure of comparisons between expected and subjectively observed effects, was correlated with placebo response (r Ā¼ 0.38, P Ā¼ 0.008). These results suggest that positive expectations of placebo analgesia, a classical mechanism for the formation of unconditioned placebo responses (Kirsch, 1985), might not be sufficient for the development of placebo responses. No sex differences were observed in these measures.…”
Section: Psychophysical Responses To Placebo Administrationmentioning
confidence: 72%
“…Expectation of placebo analgesia was not significantly correlated with placebo response (r Ā¼ 0.19, P Ā¼ 0.19), while the difference between subjectively assessed and initially expected efficacy, which represents a measure of comparisons between expected and subjectively observed effects, was correlated with placebo response (r Ā¼ 0.38, P Ā¼ 0.008). These results suggest that positive expectations of placebo analgesia, a classical mechanism for the formation of unconditioned placebo responses (Kirsch, 1985), might not be sufficient for the development of placebo responses. No sex differences were observed in these measures.…”
Section: Psychophysical Responses To Placebo Administrationmentioning
confidence: 72%
“…First, given the strong evidence that hypnosis is an effective treatment for chronic pain, coupled with its cost-effectiveness and minimal side effects [80,81], it can be concluded that hypnosis is a reasonable approach for clinicians to use for helping patients better manage with chronic pain. Second, given evidence that adding hypnosis to other treatments, such as CBT [25] or cognitive therapy [24], may enhance the efficacy of those treatments, hypnosis can be considered a reasonable adjunct to other psychological interventions. Therefore, clinicians who treat patients with chronic pain would do well to consider learning and incorporating hypnotic techniques into their practice.…”
Section: Discussionmentioning
confidence: 99%
“…for hypnosis to enhance the benefits of other psychological interventions [20,[24][25][26][27] and physical interventions, including medications and standard medical care [22,[28][29][30]. During hypnosis, individuals are given an invitation to focus their attention through an induction, followed by suggestions for change or improvement [31].…”
mentioning
confidence: 99%
“…The link between expectancies and the impact of stressful events is considered to be either direct (e.g., Kirsch, 1985Kirsch, , 1990 or indirect (e.g., mediated by coping activities; Scheier et al, 2001). The link between expectancies and physical health seems to be mediated by emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…These findings can easily be integrated into Kirsch's (1985Kirsch's ( , 1990) concept of response expectancies, which he defined as expectancies concerning the occurrence of nonvolitional responses. According to this theoretical framework, response expectancies tend to be self-fulfilling.…”
Section: Expectancies and Affect Regulationmentioning
confidence: 98%